The intensified trend of coastal upwelling in the South China Sea during 1982-2020 - Liu, Shan; Zuo, Juncheng; Shu, Yeqiang; Ji, Qiyan; Cai, Yunxia; Yao, Jinglong (Frontiers in Marine Science, 2023)
Using sea surface temperature (SST) data from satellite observations and reanalysis, we revealed the long-term trend of coastal upwelling in the South China Sea (SCS) during 1982–2020. An upwelling index (topographic position index, TPI), defined as the SST difference between the center cell and its neighbors, was used to quantify the upwelling intensity. There are three typical regions (eastern Guangdong, eastern Hainan, and eastern Vietnam) of coastal upwelling in the SCS, in which the upwelling intensity showed an increasing trend during 1982–2020. For all three regions, the upwelling intensity trend reached 0.2 °C per 10 years in the past 40 years or so. A satellite wind dataset, CCMP, and reanalysis products, ERA5 and ORAS5, were used to discuss the causes of intensified upwelling. Based on the CCMP, the enhanced upwelling in eastern Guangdong and eastern Hainan may be more related to the strengthening of the wind stress curl. Both alongshore wind stress and wind stress curl contribute to the enhanced upwelling in southern Vietnam, and the increasing trend of upwelling in northern Vietnam is not significantly related to the wind field. This study could contribute to the understanding of coastal upwelling response to the long-term climate change in a marginal sea under the background of global warming.